2010
DOI: 10.1111/j.1464-410x.2010.09274.x
|View full text |Cite
|
Sign up to set email alerts
|

Benign Prostatic Hyperplasia: Counting the Cost of Its Management

Abstract: 9 0 1 INTRODUCTION BPH is estimated to affect around 3.2 million men of middle age and beyond in the UK. BPH not only has a serious effect on the quality of life of patients and their families; the condition is also expensive for the NHS, both in terms of costs both for GP practices in primary care, and for urology services in secondary care. Moreover, BPH, especially if acute urinary retention (AUR) develops, can have a very deleterious effect on an individual's quality of life [1]. In the future the social a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 10 publications
0
37
0
1
Order By: Relevance
“…BPH-associated LUTS (LUTS/BPH) seriously impairs the quality of life of elderly men and imposes significant economic burden on society [1]. Largescale epidemiological studies have shown that men with BPH present increased risks of prostate cancer (PCa) and PCa-related mortality [2].…”
Section: Introductionmentioning
confidence: 99%
“…BPH-associated LUTS (LUTS/BPH) seriously impairs the quality of life of elderly men and imposes significant economic burden on society [1]. Largescale epidemiological studies have shown that men with BPH present increased risks of prostate cancer (PCa) and PCa-related mortality [2].…”
Section: Introductionmentioning
confidence: 99%
“…Effective treatments for LUTS, including medication use and surgery, are available. However, these treatments are expensive and contribute to the growing cost of healthcare in the United States 2 . Lifestyle factors play an important role in the etiology of LUTS 3 ; therefore, one cost-effective strategy for addressing LUTS may be to intervene on modifiable lifestyle factors before treatment becomes necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Many patients with BPH present with bothersome lower urinary tract symptoms (LUTS), typically an increase in urinary urgency and frequency, nocturia, decreased and intermittent force of stream and a sense of incomplete bladder emptying3; these symptoms can have a substantial negative impact on quality of life (QoL) 4. BPH/LUTS is a progressive condition that can lead to serious long‐term complications such as acute urinary retention (AUR) and BPH‐related surgery,5 and is associated with a considerable economic burden 6, 7, 8…”
Section: Introductionmentioning
confidence: 99%